Bernhard Brehmer & Jeanine Treffers-Daller (Eds): Lost in Transmission : The Role of Attrition and Input in Heritage Language Development - Sergei, Gnitiev (Journal Of Language Education and Development (JLed), 2020)
This book review of key contribution to the description and explanation of variability in the outcomes of heritage language acquisition, taking into account a wide range of factors which impact on language acquisition. It summarize the role of attrition and input in heritage language development from Bernhard Brehmer & Jeanine Treffers-Daller Amsterdam, Philadelphia: John Benjamins Publishing Company, 2020. vii, 276 pp.